An optimized protocol to detect ubiquitination modification of exogenous or endogenous proteins - Xinyu Li; Wei Jiang; Min Fang (STAR Protocols, 2023)
Summary: Ubiquitination modification is an important post-translational modification that regulates the stability and function of proteins. Here, we present a protocol to detect the K27-linked polyubiquitination of exogenous and endogenous mitochondrial antiviral signaling protein. We describe steps for detecting ubiquitination of exogenous protein, transfecting the encoding plasmid of the protein, and immunoprecipitating the target protein with an antibody. We then detail procedures for detecting ubiquitin of the target protein by western blot. This protocol applies to other proteins of interest.For complete details on the use and execution of this protocol, please refer to Jiang et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.